1996
DOI: 10.1006/qres.1996.0014
|View full text |Cite
|
Sign up to set email alerts
|

New Radiocarbon Dates for the Vedde Ash and the Saksunarvatn Ash from Western Norway

Abstract: The Vedde Ash Bed (mid-Younger Dryas) and the Saksunarvatn Ash (early Holocene) are important regional stratigraphic event markers in the North Atlantic, the Norwegian Sea, and the adjacent land area. It is thus essential to date them as precisely as possible. The occurrence of the Saksunarvatn Ash is reported for the first time from western Norway, and both tephras are dated precisely by AMS analyses of terrestrial plant material and lake sediment at Kråkenes. The Vedde Ash has been previously dated at sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(168 citation statements)
references
References 5 publications
11
155
0
2
Order By: Relevance
“…This layer has been independently dated by 14 C to 10,330 ± 30 BP (based on 11 AMS 14 C ages from Bard et al 1996 andBirks et al 1996), which agrees with the coral date from Tahiti (at 11,930 cal BP) only when R=300 yr is applied (Figures 4 and 5). Table 4 Mean reservoir ages of corals from Barbados and Tahiti and New Guinea (Edwards et al 1993) …”
Section: Comparison With Corals From Barbados Tahiti Mururoa and Nesupporting
confidence: 73%
See 1 more Smart Citation
“…This layer has been independently dated by 14 C to 10,330 ± 30 BP (based on 11 AMS 14 C ages from Bard et al 1996 andBirks et al 1996), which agrees with the coral date from Tahiti (at 11,930 cal BP) only when R=300 yr is applied (Figures 4 and 5). Table 4 Mean reservoir ages of corals from Barbados and Tahiti and New Guinea (Edwards et al 1993) …”
Section: Comparison With Corals From Barbados Tahiti Mururoa and Nesupporting
confidence: 73%
“…As noted by Bard et al (1998), the GRIP timescale is also confirmed through the Saksunarvatn ash layer, which has been identified in the GRIP core and dated to 10,180 (Grönvold et al 1995). This layer has been independently dated by 14 C to 8960 ± 70 BP (based on three AMS 14 C ages from Birks et al 1996), which perfectly fits the pine calibration curve (Figure 2). …”
Section: Comparison With Data From the Cariaco Basinsupporting
confidence: 58%
“…This is later than interpreted for the Sotra curve and other sea-level curves in western Norway. We consider this also to be related to the accuracy of the 14C dates, but partly also to the elevations of the investigated basins, and the original estimate of the Vedde Ash Bed Birks et al, 1996), which was 300 yr too old. Another striking effect of the improved chronology is the timing of the major post-glacial regression.…”
Section: Discussion the Younger Dryas Transgressionmentioning
confidence: 99%
“…The Vedde Ash has been dated to ca. 10 300 14C yr BP (Birks et al, 1996) and 11 980+-80 ice-core yr BP (Grønvold et al, 1995). In addition, we use the rise of Betula (birch) pollen that we regard as a reliable, local correlation horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Ingólfsson et al 1997;Geirsdóttir et al 1997). The first observation of Vedde Ash at the base of lithofacies Ssd, the transitional unit between the glacialmarine and postglacial seismic units, provides a maximum age for lithofacies Ssd of 10.3 ka BP (Birks et al 1996). We consider this to be a maximum age because we recognize that the Vedde Ash in lithofacies Ssd may not represent a primary ash-fall deposit.…”
Section: Tephra Analysismentioning
confidence: 99%